2018
DOI: 10.1534/g3.117.300504
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Two Distinct Classes of the Human INO80 Complex Genome-Wide

Abstract: Chromatin remodeling and histone modifying enzymes play a critical role in shaping the regulatory output of a cell. Although much is known about these classes of proteins, identifying the mechanisms by which they coordinate gene expression programs remains an exciting topic of investigation. One factor that may contribute to the targeting and activity of chromatin regulators is local chromatin landscape. We leveraged genomic approaches and publically-available datasets to characterize the chromatin landscape a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…2b), suggesting that it may play an important role in their regulation. This is consistent with the recent discovery that human INO80 occupies both active and repressive chromatin domains (38).…”
Section: Ino80 Occupies Bivalent Gene Promoterssupporting
confidence: 93%
“…2b), suggesting that it may play an important role in their regulation. This is consistent with the recent discovery that human INO80 occupies both active and repressive chromatin domains (38).…”
Section: Ino80 Occupies Bivalent Gene Promoterssupporting
confidence: 93%
“…In addition to DNA repair, we find a gene regulatory role for Ino80 in YY1-associated transcription. Previous studies have shown that INO80 and YY1 interact 44 , bind open chromatin 15 , and mediate transcriptional activation 17 . This role is compromised in Ino80 cKO-E, which is characterized by downregulation of YY1-associated genes.…”
Section: Discussionmentioning
confidence: 98%
“…We therefore concluded that linc‐MYH specifically controls the function of INO80 in the regulation of MuSC abundance and proliferation but not in DNA repair. The data also suggest that the linc‐MYH‐dependent function of INO80 might rely on YY1, which is a known interactor of the INO80 complex (Cai et al , 2007; Wu et al , 2007; Chen et al , 2011; Runge et al , 2018).…”
Section: Resultsmentioning
confidence: 94%